TRANFORMASI PEMBAYARAN ELEKTORNIK DI INDONESIA DAN IMPLIKASINYA TERHADAP KEMAJUAN BISNIS KREATIF BERBASIS DARING DI WILAYAH EKS-KERESIDENAN BESUKI - Randika Fandiyanto; Karnadi Karnadi (Relawan Jurnal Indonesia, 2019)
The development of digital technology cannot be dammed by the development of the times, added from the processing industry to the industry in the financial sector. The high level of competition requires a lot of choices to encourage each other to advance some other sectors as well as undertaking massive transformation. The purpose of this study is first, to describe the development of electronic payments over the period 2015 to 2018. Second, to explore the development of electronic payments towards the progress of MSMEs in Situbondo. Third, which is to define the implications of digitizing payments to payment systems in the Situbondo district. Implications for the Progress of Creative Business Based in the Besuki Ex-Residency Area, marketing can be easily accessed to get a wide range of new customers. Aside from that, the increasingly sophisticated technology currently dealing specifically with the transaction system has started to decline from the beginning of the 2015 online transaction system which started from social media to the e-commerce platform. Proven number of new SMEs in the Ex-residency area of ​​Besuki continues to grow extraordinary at this time, by offering various types of creative products on various ecommerce platforms in Indonesia.